Cancer story - Kidder, Tom; Dartmouth-Hitchcock Medical Center production; Films for the Humanities & Sciences (Princeton, N.J. : Films for the Humanities & Sciences, 2004)
This four -part series sets the medical and personal complexities of cancer into an easily understood framework. Designed to facilitate decisions involving the disease, whether those decisions are preventive in nature or are part of a treatment process
Title from title screen
Executive producer, Jamie Guth ; editor, John Garmiey ; camera, Gino Bruno...[et al.]
Narrator: Jamie Guth
Keywords: Cancer; Cancer cells -- Growth; Cancer -- Prevention; Cancer -- Patients -- Case studies; Cancer -- Research